DEVELOPMENT OF OMNIBUS LAW ON MARINE SECURITY AND ITS INFLUENCE IN REGULATION OF AUTONOMOUS MARINE VEHICLE (AMV) - Silviani, Ninne Zahara; tianto, Agus; Rahayu, Putri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Technology cannot be separated from the maritime sector with the discovery of unmanned vessels or AMVs as a use option for various purposes. AMV technology is considered capable of providing various benefits commercially and for the security of a region. However, its development has not been followed by specific regulations, including in Indonesia. In line with this, Indonesia still has overlapping issues related to maritime security law. So a solution is needed to handle this. The method for writing this research uses a normative legal method with a conceptual and regulatory approach. The research results show that the maritime security omibus law is the government's solution in synchronizing overlapping regulations between applicable agencies with the formation of PP Number 13 of 2022 concerning maritime security. The maritime security omnibus law is still being developed until it will eventually touch on statutory regulations. In line with this, AMV technology is expected to be part of this arrangement.